Evaluation Research on Diniyah Formal Early Implementation in Pesantren - Munawiroh, Munawiroh; Dudin, Achmad; Hasan Basri, Husen; Ta’rif, Ta’rif (Riviera Publishing, 2022)
Introduction: The government and Islamic boarding schools strategically improve the quality of the implementation of Formal Diniyah Education, known as Formal Diniyah Education (PDF), professionally and effectively. In this regard, Islamic boarding schools and the government must prepare policies on PDF development. However, PDF in Islamic boarding schools is not optimal, so it is strategic to be evaluated as material for improving the quality of PDF in Islamic boarding schools in the future. Method: This evaluation research uses a qualitative approach by taking cases from several PDFs in the pilot project of Indonesian Islamic boarding schools. Result: Among the research findings, it is stated that: The level of PDF quality is primarily determined by the optimal level and whether PDF implementation in Islamic boarding schools is exemplary. Among the findings: the recognition of PDF in Islamic boarding schools must be accompanied by professional monitoring of the quality context of the application of PDF in Islamic boarding schools, the PDF curriculum still overlaps with Ma'had Ali's curriculum, lack of learning management and lack of optimal professional guidance for PDF, PDF achievements of non-Muslims. Academic (psychomotor) in pesantren is not too much attention. Conclusion: The government and Islamic boarding schools need to pay attention to the effectiveness of the application of PDF in Islamic boarding schools so that the quality of PDF in Islamic boarding schools is always maintained, through several strategic efforts, namely: in collaboration with the Ministry of Religion, Balitbang need to recommend to Pusdiklat and Pusdiklat, and pesantren need to pay attention to the optimal performance of students PDF at the boarding school.